The gift in you : discover new life through gifts hidden in your mind - Leaf, Caroline, 1963- (Southgate, TX: Inprov, 2009)
A follow-up to the author's Who switched off my brain?, providing a biblical approach to self-actualization. No matter what you may have been told, the tests that you may have taken, or what you may believe about yourself - you have a unique gift inside of you that can change the world., what does God say about your gift? And how does neuroscience prove that you are uniquely equipped to fulfill your purpose? In this ground-breaking book, Dr. Caroline Leaf illustrates the revolutionary link between brain science and God's purpose for each one of us.
Keywords: Thought and thinking -- Religious aspects -- Christianity; Self-actualization (Psychology) -- Religious aspects -- Christianity; Well-being -- Religious aspects -- Christianity; Positive Psychology